Green Choices : A Qualitative Study of Online Personal Care Products’ Purchasing Behavior - Panwar, Nikita; Shetty, Dasharathraj K.; Shenoy, Sandeep S.; Kumar, Anuj (Indian Journal of Marketing, 2025)
Purpose : This study examined the antecedents of green purchase behaviour in e-commerce for personal care products. Given the increasing importance of sustainable consumption and the relatively low adoption of GPCPs online, the study sought to develop a deeper behavioural understanding that can support strategies for increasing green consumption. Methodology : A qualitative study was conducted using Clarke and Braun’s thematic analysis technique. Data were gathered through semi-structured interviews and analyzed in order to identify consumer patterns and insights into environmentally-minded consumption behaviour. Findings : There were eight major themes found in this study: Green Empowerment, Eco-Conscious Motivation, Sustainable Shopping Delight, Green Product Accessibility, Eco-Transparency, Social Influence, Green Quality Assurance, and Cost-Value-Balance. These themes were integrated into a holistic model that incorporates contextual factors, supplier characteristics, and regulatory requirements that influence the environmentally-conscious online shopping of personal care products. Implications : These findings provided useful insights to e-commerce platforms, sustainable personal care brands, and policymakers. The study highlighted the importance of improving product accessibility, enhancing product information, and streamlining the online shopping process for consumers. Originality : This study addressed a major gap in sustainable consumption literature by offering qualitative insights into GPCP purchasing, a high-use category that remains under-researched in online contexts. The study also proposed a model that integrated emotional benefits, empowerment mechanisms, and e-commerce - specific transparency and accessibility factors into a single framework not addressed in prior research.